Islamic Banks versus Commercial Banks and Performance: The Context of Saudi Arabia? (Global Journal of Management and Business Research, 2014)
Making a comparative analysis between conven-tional and Islamic banks, this paper examines which bank characteristics and macroeconomic environment affect the bank performance in Saudi Arabia. We estimate a linear panel date model using Prais-Winsten technique for 12 Saudi conventional and Islamic banks over the period 2005-2011. The findings suggest that low cost, high capital adequacy and low inflation rate improve the levels of Saudi conventional bank performance. However, high performance in Saudi Islamic banks requires better asset quality, higher capital adequacy, lower cost, higher bank weigh and higher number of branches.
Keywords: financial accounting; saudi bank perfor-mance; islamic versus conventional banks; prais-winsten method